Neuropeptide Y Stimulates Food Intake in the Zebrafish, Danio rerio - Yokobori, E.; Azuma, M.; Nishiguchi, R.; Kang, K. S.; Kamijo, M.; Uchiyama, M.; Matsuda, K. (WILEY, 2012)
Neuropeptide Y (NPY) is a potent orexigenic neuropeptide implicated in feeding regulation in mammals. However, except for the case of the goldfish, the involvement of NPY in the feeding behaviour of teleost fish has not well been studied. Therefore, we investigated the role of NPY in food intake using a zebrafish (Danio rerio) model because the molecular bases of NPY and its receptor have been well studied in this species. We examined the effect of feeding status on NPY-like immunoreactivity and the expression level of the NPY transcript in the brain. The number of neuronal cells showing NPY-like immunoreactivity in the hypothalamic regions, including the periventricular nucleus of posterior tuberculum and the posterior tuberal nucleus, was significantly increased in fish fasted for 7 days. NPY mRNA levels in the hypothalamus, but not the telencephalon, obtained from fish fasted for 7 days were higher than those in fish that had been fed normally. We then investigated the effect of i.c.v. administration of NPY on food intake. Cumulative food intake was significantly increased by i.c.v. administration of NPY (at 1 and 10 pmol/g body weight; BW) during a 60-min observation period. The NPY-induced orexigenic action (at 10 pmol/g BW) was blocked by treatment with a NPY Y1 receptor antagonist, BIBP-3226, at 100 pmol/g BW. These results indicate that NPY acts as an orexigenic factor in the zebrafish.
Keywords: OREXIN-A; CHROMOSOME DUPLICATIONS; CARASSIUS-AURATUS; GOLDFISH; BRAIN; NPY; RECEPTORS; EVOLUTION; GENOMICS; CHOLECYSTOKININ